1976
DOI: 10.1038/bjc.1976.155
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages and lymphoid tissues in mice with concomitant tumour immunity

Abstract: Summary.-The growth in mice of subcutaneous isografts of any of 5 methylcholanthrene-induced fibrosarcomas was associated with macrophage stimulation, reflected in an increased incidence of DNA-synthesizing cells among macrophages in the uninjected peritoneal cavity. This occurred at some stage with 4 tumours that induced concomitant immunity and one that did not. Some degree of splenomegaly also occurred with all 5 tumours. The spleens of all the tumour-bearing mice showed histological evidence of increased h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

1977
1977
2002
2002

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…The general decline in the proportion of cells expressing T cell markers in the spleens of mice with MC-2 tumours might in part be explained by an expansion of non-T cells associated with splenomegaly. Splenomegaly occurs in mice carrying any of a number of independently derived methylcholanthrene-induced fibrosarcomas, and is coincident with haemopoiesis and plasmacytopoiesis (32). Spleen weights, and the number of splenic leucocytes recoverable from mice with large MC-2 tumours, can be more than twice those in normal littermates (23, and unpubl.…”
Section: Discussionmentioning
confidence: 99%
“…The general decline in the proportion of cells expressing T cell markers in the spleens of mice with MC-2 tumours might in part be explained by an expansion of non-T cells associated with splenomegaly. Splenomegaly occurs in mice carrying any of a number of independently derived methylcholanthrene-induced fibrosarcomas, and is coincident with haemopoiesis and plasmacytopoiesis (32). Spleen weights, and the number of splenic leucocytes recoverable from mice with large MC-2 tumours, can be more than twice those in normal littermates (23, and unpubl.…”
Section: Discussionmentioning
confidence: 99%
“…Circulation of sensitized lymphocytes also explains the presence of concomitant immunity. As in other murine systems [14,15,16] the concomitant immunity in the SL2-bearing DBA/2 mouse would be divided into two phases. The first phase was tumor specific and has been ascribed to tumor specific Tcells in cooperation with macrophages [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…This dif ference might be explained by their extensive use of a Moloney sarcoma-induced tumor [32] as opposed to our methylcholanthrene-induced fibrosarcoma. Results from the work of Nelson and Kearney [33][34][35] using methylcholanthrene-induced tumors, indicated that there is a link between activated TBM Mg and enhance ment (not inhibition) of splenic T cell activity. It is also possible that the inhibition seen by Herberman's group could be due to a purely quantitative increase in the number of Mg seen by us [17] and others [36] in TBM.…”
Section: Discussionmentioning
confidence: 99%